Development of wireless engine lubrication oil life alert system - Tin, Shaw Liang (2015)
Engine lubricant plays a significant role in reducing internal friction between the piston and shear of moving mechanical parts. Besides, it also improves engine performance and efficiency. Rapid developments in engine oil monitoring systems have taken place to determine that the engine lubricant degradation level is attuned towards reducing unnecessary engine power loss and maintenance cost. However, the accuracy of the engine monitoring systems can be affected by surrounding conditions, such as temperature, pressure and lubricant content whereas the conventional oil-changing strategy according the distance travelled is not efficient as the rate of oil degradation is different based on the type of a vehicle and its usage objective. Hence, the development of this wireless engine lubricant oil change alert system (Wi-LoCAS) in this research is fully controlled by microcontroller. The proposed system is capable of determining the total revolution experienced by the engine even at high revolution of the engine and able to predict a maximum lifetime supposed to be limited for the type of engine oil used by using the proposed oil change algorithm, MAXREV=(1.2)(highest gear ratiotire circumference)×distance travelled. The design was simulated using a microcontroller simulation package, Proteus 7 and its functionality was tested on a specially designed test rig. This system was also installed in two real cars to further validate its performance. The findings indicate that, this system is capable of predicting the engine lubricant lifetime precisely without being affected by the surrounding condition when the engine is operating.